Prediction of performances in ski-jumping in-run and take-off phase modeling as a support for training in wind tunnel - Coulmy, N.; Lamy, K.; Perraudin, M. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: Optimization of technique to improve performance in ski jumping is a complex process to which a wind tunnel can contribute data and understanding. In ski jumping, take-off action is one of the most important factor. Coaches and athletes are confronted with the problem of assessing the efficiency of different motion strategies. Mathematical models may provide an adequate solution to confronte objective data and athletes perception in condition of wind. The purpose of this work is conducted to develop a simplified mathematical model of in-run, take off and early flight phase performance in ski jumping as a support for training sessions of athletes in a wind tunnel,